The Relationship of Oceanography Factors to The Presence of Marine Resources in the Fish Apartment Installation Area in Takalar Waters - Wayan Kantun; Arwin Adi Wahyudi; Rahmat Januar Noor (LPPM Institut Teknologi dan Bisnis Maritim Balik Diwa, 2025)
Oceanographic parameters are benchmarks for determining the existence and presence of marine resources in a waters. This study aims to analyze oceanographic parameters with the presence of marine resources in the fish apartment installation area. This research is classified as a quantitative research with data collection through observation, by making objective observations, and visually through underwater cameras. The results showed that the value of oceanographic parameters had a positive correlation with the presence of marine resources in fish apartment areas. The presence of marine resources was 725 individuals with 11 species, the proportion of presence of resources seen from the distribution of morning and evening time was 643 individuals (88.69%) and 82 individuals (11.31%) and was dominated by flying fish (Decapterus sp). Based on oceanographic factors, the parameters of temperature, current velocity, pH, and salinity and brightness have the most influential correlation values ​​for the presence of marine resources in fish apartment areas. Oceanographic factors greatly determine the presence of fish in the fish apartment installation area.